ANALISIS KEBIJAKAN DALAM PENGENDALIAN KASUS GIGITAN HEWAN PENULAR RABIES (GHPR) PADA MANUSIA DI KOTA PEKANBARU - Egawati, Egawati; Rustam, Musfardi; Abidin, Zainal; Alamsyah, Agus; Renaldi, Reno (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Rabies is a deadly disease with Case Fatality Rate (CFR) of 100%. In Riau Province, the number of cases of Rabies Transmitting Animal Bites (RTAB) has increased by about 5 percent every year. Pekanbaru City was area with high RTAB. The purpose of research was to determine policy analysis in controlled cases of animal bites that transmit rabies to humans in Pekanbaru City in 2022. The methode of research used qualitative analysis with a research design approach of Rapid Assessment Procedure (RAP). The data analysis used content analysis. The Collecting data used observation methods, document checked and in-depth interviews processed by triangulation. The results of the study revealed that the handling of RTAB cases had not all gone well, the number of human resources was still lacking, There is low training in capacity building in the Integrated Bite Case Management. The implementation of public education is rarely carried out and is only combined with other program. The tools such as leaflets and brochures were only available in a small number of services. The implementation of education to the public, an integrated rabies control system and monitoring evaluation of rabies control were carried out in conjunction with other programs. It can be concluded that in order to assess the success of a rabies control program, it is necessary to improve the implementation of monitoring and evaluation from planning to implementation, so that the location of obstacles that occur in the field can be known.Keywords: Rabies Infecting Animal Bite, Human Resources, Education, Monitoring Evaluation